Evaluasi Penyimpangan Penggunaan Lahan Berdasarkan Peta Arahan Pemanfaatan Lahan di Kecamatan Ubud, Kabupaten Gianyar, Provinsi Bali - FRANSISKA PURBA; R. SUYARTO; I WAYAN NUARSA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Evaluation of Deviation Land Based On The Direction Of Land Use In Ubud District, Gianyar Regency, Province of BaliUbud District is one of the most important tourist destinations in Bali for local domestic and international tourist.Development of tourism area near to build their infrastructure such as hotel, villa, restoran, spa, etc. Currently, many tourism facilities was development in high slope, this can cause natural hazard such as land sliding, erosion, flood, etc. The objective of this result is to compare between directions of land use and existing land use. Calculations of land use directions used the scoring system with 3 variable, that is tabel of daily rain fall, slope, and soil type. The existing land use was obtained by screen digitizing of quickbird image in 2014 to produce land use map. The direction of land use in Ubud district consists of, the area of seasonal cultivation and settlements area 2975,45 hectares (68,16%), perrenial crop cultivation area 1256,44hectares (28,78%), and the buffer area 133,34 hectares (3,06%). Interpretation result and classification of Quickbird Imagery by the year of 2014 for the land use in Ubud District consists of settlement area, 1523,19 hectares (34,89%), rice irrigation area of 1673,44 hectares (38,33%), moor 798,16 hectares (18,28), mixed-use cultivation area 301,46hectares (6,91%), and monkey forest/river border protected areas 68.98 hectares(1,59%).Image classification accuracy in this study is 92,30%. The discrepancy in the land use direction that showed better use of the region consists of: the seasonal cultivation and the settlement area became an monkey forest/river border protected areas 49,49 hectares(1,13%), perennial crop cultivation area became an monkey forest/river border protected areas8,18 hectares (0,18%), area of seasonal crop cultivation and settlements area into mixed-use cultivation area 146,70 hectares (3,36%). Meanwhile, the discrepancy in the use land direction that became worse consists of: buffer area into a settlements area 83,69 hectares (1,91%), buffer area into rice paddies covering 11,04 hectares (0,26%), buffer area into an area of moor 25,25 hectares (0,57%),buffer area into the mixed-use cultivation area 2,06 hectares (0,04%), perennial cultivation area into settlements covering 335,53 hectares (7,69%), perennial cultivation area into rice paddies covering an area of 369,34 hectares (8,46%), perennial cultivation area into an moor area 390,81 hectares(8,96%).